The Effects of Leadership Styles on Job Performance: A Case Study in the Ministry of Telecommunications in Yemen - Alhusaini, Salma Shaif Ali (2012)
The main purpose of this study is to examine the relationships between transformational and transactional leadership with job performance that consists of the employees in the Ministry of Telecommunications in Yemen. This paper discusses the effect of leadership types on consists. In other words, the study attempts to investigate whether there is a significant relationship between leadership style and job performance in selected Ministry of Telecommunications in Yemen. The number of respondents is 120 managers of employees in the Ministry of Telecommunications in Yemen using a structured questionnaire. The data was analyzed using SPSS 19.0. Three main hypotheses were tested using Pearson product-moment correlation coefficient. Their perspectives were translated into reports based on transformational and transactional leadership. Based on regression analysis, there are all independents variable, transformational and Transactional leadership that affecting the Ministry of Telecommunications performance in Yemen.